Surface adherence and vacuolar internalization of bacterial pathogens to the Candida spp. cells: Mechanism of persistence and propagation - Fazlurrahman Khan; Geum-Jae Jeong; Aqib Javaid; Dung Thuy Nguyen Pham; Nazia Tabassum; Young-Mog Kim (Journal of Advanced Research, 2023)
Background: The co-existence of Candida albicans with the bacteria in the host tissues and organs displays interactions at competitive, antagonistic, and synergistic levels. Several pathogenic bacteria take advantage of such types of interaction for their survival and proliferation. The chemical interaction involves the signaling molecules produced by the bacteria or Candida spp., whereas the physical attachment occurs by involving the surface proteins of the bacteria and Candida. In addition, bacterial pathogens have emerged to internalize inside the C. albicans vacuole, which is one of the inherent properties of the endosymbiotic relationship between the bacteria and the eukaryotic host. Aim of review: The interaction occurring by the involvement of surface protein from diverse bacterial species with Candida species has been discussed in detail in this paper. An in silico molecular docking study was performed between the surface proteins of different bacterial species and Als3P of C. albicans to explain the molecular mechanism involved in the Als3P-dependent interaction. Furthermore, in order to understand the specificity of C. albicans interaction with Als3P, the evolutionary relatedness of several bacterial surface proteins has been investigated. Furthermore, the environmental factors that influence bacterial pathogen internalization into the Candida vacuole have been addressed. Moreover, the review presented future perspectives for disrupting the cross-kingdom interaction and eradicating the endosymbiotic bacterial pathogens. Key scientific concepts of review: With the involvement of cross-kingdom interactions and endosymbiotic relationships, the bacterial pathogens escape from the environmental stresses and the antimicrobial activity of the host immune system. Thus, the study of interactions between Candida and bacterial pathogens is of high clinical significance.